Managing Complex Production System Variables - Tan, Kim Hua; Tesic, Zdravko (International Journal of Industrial Engineering and Management, 2013)
Managing a large number of production variables’ information is a complex task. So far, little is available to assist production managers to manage and visualise variables’ information in such a way that these valuable variables information could be used to support strategic decision making. This research has sought to address this problem by developing a software tool that offers a database, and visualisation function, which shows the inter-relationships of the production variables. The tool was developed based on the Connectance Concept, and has a built-in evaluation module using the Analytic Hierarchy Process to facilitate decision analysis. This paper describes the structure of the software tooland its features. The results of testing and application ofthe tool in companies are presented. This paper concludes by discussing the implications of this research for managers, and identifying directions for future research. Article history: Received (21 February 2013); Revised (10 May 2013); Accepted (27 May 2013)